2012
DOI: 10.3892/ijmm.2012.947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circulating CD4+CD25+ and liver-infiltrating Foxp3+ cells in HCV-associated liver disease

Abstract: Abstract. In hepatitis C virus (HCV)-associated liver disease, the immune system is unable to clear the viral infection. Previous studies have raised the possibility of an involvement of regulatory T cells (Tregs) + cells in the liver infiltrates showed significantly higher proportions of peripheral CD4 + CD25 low cells. Moreover, we found lower serum transaminase levels in the patients than in the controls, as shown by Foxp3 + immunohistochemistry, although these results were only statistically significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recent data from our laboratory have suggested that colonic T reg cells are negatively correlated with liver inflammation and HCV viral load, which supports a strong linkage between gut-derived T reg and HCV infection [35, 36]. T reg cells appear to assist in the maintenance of chronicity by inhibition of anti-HCV immune responses and consequently attenuate the intrahepatic tissue-damaging response to infection [26, 32]. …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent data from our laboratory have suggested that colonic T reg cells are negatively correlated with liver inflammation and HCV viral load, which supports a strong linkage between gut-derived T reg and HCV infection [35, 36]. T reg cells appear to assist in the maintenance of chronicity by inhibition of anti-HCV immune responses and consequently attenuate the intrahepatic tissue-damaging response to infection [26, 32]. …”
Section: Introductionmentioning
confidence: 87%
“…In cases of chronic hepatitis C (CHC), there is evidence that the frequency of T reg cells is higher than in controls and is negatively correlated with the necro-inflammatory score [2931]. The elevated frequency of T reg cells may explain the weak HCV-specific T-cell responses in CHC [32]. Moreover, there is some evidence that individuals with CHC may harbour more T reg cells in their peripheral circulation [33] and in the liver than those uninfected [34].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic HCV cases have an increased frequency of T reg cells compared to controls and the T reg cells negatively correlated with the degree of inflammation [ 76 78 ]. The higher frequency of T reg cells may also explain the weak HCV-specific T-cell responses in chronic HCV patients [ 79 ]. There is also some evidence that chronic HCV patients may harbour more T reg cells in their peripheral circulation [ 80 ] and in the liver than those who are uninfected [ 81 ].…”
Section: Reviewmentioning
confidence: 99%
“…There is also some evidence that chronic HCV patients may harbour more T reg cells in their peripheral circulation [ 80 ] and in the liver than those who are uninfected [ 81 ]. Thus, T reg cells appear to assist in the maintenance of chronic infection by inhibiting anti-HCV responses and, therefore, attenuating the intrahepatic tissue-damaging response to infection [ 79 , 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…(Fiore et al 1997; Koziel and Walker 1997). T-regulatory cells were extensively studied by various groups and considered to be involved in the induction of tolerance to viral antigens in affected hosts (Amoroso et al 2012; Miyaaki et al 2009). On the contrary, NK cells were found to be suppressed by HCV proteins (Cheent and Khakoo 2011; Varchetta et al 2012; Wen et al 2008).…”
Section: Introductionmentioning
confidence: 99%